EP1230 Development of a pragmatic assay to assess homologous recombination competency in endometrial cancer. (1st November 2019) - Kramer, CJH; van Wijk, LM; de Jonge, MM; Serra, V; Llop-Guevara, A; de Kroon, CD; Vreeswijk, MPG; Bosse, T
Abstract : Introduction/Background: Homologous recombination deficiency (HRD) is frequent in non-endometrioid endometrial cancer (EC), justifying clinical trials testing PARP-inhibitors. To facilitate this development a pragmatic test to asses HR competency is required. Accumulation of RAD51 protein at sites of DNA double strand breaks, has been put forward as a reliable functional test for HR competency. Here we aimed to test the performance of this pragmatic assay on formalin-fixed paraffin-embedded (FFPE) tumour tissue. Methodology: We used a previously described, prospective collected series of 21 EC that underwent primary resection with known HR status based on genomic analyses (next-generation sequencing for HR-core genes and array comparative genomic hybridization/SNP array) as our training cohort. To assure the presence of endogenous DNA damage, a gamma-H2AX staining was performed. Co-immunofluorescence (IF) was performed for both Geminin (marker staining cells in G2/S phase) and RAD51. RAD51 score was calculated as the fraction of Geminin positive cells that showed RAD51 foci (≥ 2) in the nucleus. Final RAD51 scores were correlated to known HR-status. Results: All 21 EC showed positivity for gamma-H2AX staining assuring presence of endogenous DNA damage in routine diagnostic FFPE tumour tissue. Among all cases, the RAD51scores varied form 0–72%. The range of RAD51 scores in the five HRD EC was 0–4%, whereas the 16 HRP EC tested showed RAD51 scores ranging from 16–72% ( P <0.001). Conclusion: This RAD51 assay can successfully be performed on diagnostic FFPE material and reliably determined HR competency in 100% of our EC cases using cut-off RAD51 score of 10%. We will present the performance of this cut-off on our test-set of HR-annotated EC. This RAD51 assay is a promising cheap, pragmatic assay that can be used in the clinic to select patients that may benefit from platinum compounds and PARP-inhibitor therapy. Disclosure: Nothing to disclose.